The Treponema denticola Major Sheath Protein Is Predominantly Periplasmic and Has Only Limited Surface Exposure - Caimano, Melissa J. (American Society for Microbiology, 1999)
The recent discovery that the Treponema pallidum genome encodes 12 orthologs of the Treponema denticola major sheath protein (Msp) prompted us to reexamine the cellular location and topology of the T. denticola polypeptide. Experiments initially were conducted to ascertain whether Msp forms an array on or within the T. denticola outer membrane. Transmission electron microscopy (EM) of negatively stained and ultrathin-sectioned organisms failed to identify a typical surface layer, whereas freeze-fracture EM revealed that the T. denticola outer membrane contains heterogeneous transmembrane proteins but no array. In contrast, a lattice-like structure was observed in vesicles released from mildly sonicated treponemes; combined EM and biochemical analyses demonstrated that this structure was the peptidoglycan sacculus. Immunoelectron microscopy (IEM) subsequently was performed to localize Msp in T. denticola. Examination of negatively stained whole mounts identified substantial amounts of Msp in sonicated organisms. IEM of ultrathin-sectioned, intact treponemes also demonstrated that the preponderance of antigen was unassociated with the outer membrane. Lastly, immunofluorescence analysis of treponemes embedded in agarose gel microdroplets revealed that only minor portions of Msp are surface exposed. Taken as a whole, our findings challenge the widely held belief that Msp forms an array within the T. denticola outer membrane and demonstrate, instead, that it is predominantly periplasmic with only limited surface exposure. These findings also have implications for our evolving understanding of the contribution(s) of Msp/Tpr orthologs to treponemal physiology and disease pathogenesis.